Paper plate masks and tin can totem poles: A documentary analysis of Ontario elementary school visual arts curriculum and support documents form 1985 to 1998 for representations of a multicultural perspective - Godward, Julie (University of Ottawa (Canada), 2008)
This documentary analysis study critically examines representations of a multicultural perspective in selected Ontario elementary school visual arts curriculum and support documents. The study focuses on five documents that were published between 1985 and 1998, a period that coincides with important curricular changes in art education. This period was also significant with regards to developments that occurred in this province relating to multicultural education. To complete this analysis, references to race, ethnicity and culture were examined in order to identify ways in which they were being utilized in the documents. Furthermore, these references were analyzed from the perspective of critical multiculturalism to determine how multicultural education was being represented in the resources. I argue that while certain efforts were made to include a multicultural perspective in art education during this time period, these were for the most part inadequate in that they tend to present information out of context, fail to include diverse perspectives, overemphasize certain groups to the detriment of others, and perpetuate false information and stereotypes. I also contend that these deficiencies in art education are closely related to the political context that influenced the role and place of art education within the educational system.
Keywords: Education, Art.; Education, Bilingual and Multicultural.; Education, Elementary.